Wear behavior of chromium nitride coating in dry condition at lower sliding velocity and load - Singh, S.; Chattopadhyaya, S.; Pramanik, Alokesh; Kumar, S. (Springer, 2018)
The wear behavior of the chromium nitride (CrN) coating on piston ring material against liner material was investigated under dry conditions at room temperatures. Cat iron alloy, widely used in manufacturing of piston rings and cylinder liners, was coated by physical vapor deposition method. Wear tests were carried out on a Pin-on-Disc tribometer. Simultaneous effect of sliding velocities (0.3, 0.4, 0.6, and 0.8 m/s) and corresponding loads (10, 20, 30, and 40 N) on wear rate, friction coefficient, and temperature was analyzed. In conclusion, specific wear rate is decreasing by increase in load and velocity. The rise of temperature is 28 to 42 °C at the wear track room temperature resulting in a reduced coefficient of friction (COF) when the increase of load if from 10 to 40 N. The wear mechanism is a combination of mild to severe wear, three-body abrasion, and oxidation wear for dry conditions.